Analisis Penerapan ISAK No.35 Laporan Keuangan Entitas Non Laba Pada Masjid Agung Surakarta - Fadhillah, Rizka Ummu; Susanti, Ari (FEB Universitas Maritim Semarang, 2024)
The purpose of this study is to find out the form of financial statements and to find out the implementation of ISAK No.35 in the Financial Statements at the Great Mosque of Surakarta. The method used is descriptive qualitative data analysis. The data source uses primary and secondary data collected by researchers using interview, observation and documentation techniques. The researcher conducts data analysis by collecting data, reduce, presenting with the final stage of drawing conclusions. The results of the study show that the financial records of the Great Mosque of Surakarta are known to have a surplus and cash deficit every month. Analysis of the implementation of ISAK No.35 for the preparation of mosque financial statements was not found in the presentation standards carried out in 2023. At the end of the research to prepare the financial statements of the Great Mosque of Surakarta through the implementation of ISAK No.35, a more structured and detailed financial report was made for the entire mosque's finances, not only in terms of cash income and expenditure in the research.